Os (re)desenhos e memórias da igreja Senhor do Bonfim no Alto do Cruzeiro, na cidade de Feira de Santana – Bahia, entre os anos de 2012 e 2023 - Santos, Taniely da Silva (2024)
Senhor do Bonfim church, at the top of Alto do Cruzeiro (high mountain of the cruise), in Feira de Santana, Bahia, Brazil, is one of the Feira de Santana's symbols because its religious and cultural importance and its favorable location in the city. This research has the objective discuss the changes that happened between 2012 and 2023. The challenge of this study through photographs of the church and how the changes occurred in the internal and external parts as well as around the church too that caused the nowadays views. The analysis of the photos from its history time and additional documents such as heritage, newspaper and minutes helped the thinking of Pierre Nora, Jacques Le Goff (1990), Maurice Halbwachs (1990), Ulpiano Bezerra de Meneses (1992), Michael Pollak (1989) e Sandra de Cássia Araújo Pelegrini (2007), since they Cruzeiro church, as popular known by the city people, can mediate the relationship among memory, forgiveness, destruction and preservation.